Characteristics of elongated and ruptured anterior cruciate ligament grafts: An analysis of 21 consecutive revision cases - Kohei Iio; Eiichi Tsuda; Harehiko Tsukada; Yuji Yamamoto; Shugo Maeda; Takuya Naraoka; Yuka Kimura; Yasuyuki Ishibashi (Elsevier, 2017)
Background/objective: Anterior cruciate ligament (ACL) reconstructions often fail without graft rupture. The purpose of this study was to compare the characteristics of patients with elongated and ruptured bone-patellar tendon-bone (BTB) grafts that required revision surgery. Methods: Twenty one patients who required revisions of a BTB-reconstructed ACL between 2010 and 2015 were enrolled in this study. All patients were evaluated for bone tunnel position using computed tomography. Tunnel angle was calculated with radiographs. Stability under anaesthesia, and meniscus and cartilage condition were evaluated during the revision surgery. Age at primary surgery, time between primary and revision surgery, activity level, original tunnel position of the graft, and meniscus and cartilage condition were compared between elongated and ruptured grafts. Results: Age at primary surgery was not significantly different between the two groups (p = 0.528). Time between primary and revision surgery as well as activity level were also not significantly different between the two groups (p = 0.010 and p = 0.307, respectively). Femoral bone tunnel position was more proximal (p = 0.003), and radiographic tunnel angle was not significantly different between the two groups (p = 0.029). The rupture group was significantly more unstable on the pivot shift (p < 0.003). Meniscus degeneration, meniscus tear, and cartilage damage were not significantly different between the two groups (p = 0.030, p = 0.311, and p = 0.505, respectively). Conclusion: The location of the original femoral tunnel was more proximal in patients with elongated grafts than in those with ruptured grafts. Different bone tunnel position from native ACL might lead to graft elongation.